Utility of GATA3 immunohistochemistry for diagnosis of metastatic breast carcinoma in cytology specimens. Issue 4 (4th August 2014) - Braxton, David R.; Cohen, Cynthia; Siddiqui, Momin T.
<x xml:space="preserve">Abstract</x> Background GATA3 as a diagnostic marker of metastatic breast carcinoma in cytology specimens has not been fully established. Methods Metastatic breast carcinoma was assessed for GATA3, mammaglobin, and GCDFP‐15 immunohistochemistry on cell blocks. GATA3 was scored by intensity (0, negative; 1, weakly positive; 2, moderately positive; 3, strongly positive), and area (0–100%). Mammaglobin (MMG) and GCDFP‐15 staining was scored qualitatively (positive vs. negative). Results were correlated with specimen type (fine‐needle aspiration vs. body fluid), breast prognostic markers estrogen receptor (ER), progesterone receptor (PR), Her‐2/Neu (Her2), and Ki67, and with each other. Statistical significance was determined by chi‐squared test and ANOVA for numerical variables. Alpha was set as 0.05. A total of 40 CB specimens containing metastatic breast carcinoma were studied. Results GATA3 was positive in 32 (80%) cases. All ER‐positive cases (n = 25) were positive for GATA3. Conversely, all GATA3‐negative cases (n = 8) were triple‐negative breast cancers. On qualitative univariate analysis, GATA3 was statistically associated with ER (P = 0.0001), and PR (P = 0.0468). GATA3 intensity was statistically associated with ER (P ≤ 0.0001), PR (P = 0.0157), Her2 (P = 0.0256), and cancer category (P = 0.0127). GATA3 staining was statistically associated with ER (P ≤ 0.0001), PR (P = 0.0160), Her2 (P = 0.0451), and cancer category (P = 0.0002). MMG and GCDFP‐15 were directly compared to GATA3 in 35 samples. The sensitivity was 86% for GATA3, 26% for MMG, and 14% for GCDFP‐15. Conclusion GATA3 is a more sensitive diagnostic marker of metastatic breast carcinoma in CB samples than MMG and GCDFP‐15. Diagn. Cytopathol. 2015;43:271–277. © 2014 Wiley Periodicals, Inc.